Multi-Sensory Microphones for Robust Speech Detection, Enhancement, and Recognition - Zhang, Zhengyou; Liu, Zicheng; Sinclair, Mike; Acero, Alex; Deng, Li; Droppo, Jasha; Huang, Xuedong; Zheng, Yanli (Proceedings of the IEEE International Conference on Acoustics, Speech, and Signal Processing, Montreal, Canada, May 2004, 2004)
In this paper, we present new hardware prototypes that integrate several heterogeneous sensors into a single headset and describe the underlying DSP techniques for robust speech detection, enhancement and recognition in highly non-stationary noisy environments. We also speculate other business uses with this type of devices.